Do Political Connections Affect Stock Price Crash Risk-Based on Empirical Evidence from China’s Capital Market - Keping Wu (Forest Chemicals Review, 2021)
Using data from China’s capital market, the intrinsic relationship between political connections and crash risk is tested. Empirical research find that political connections and crash risk are significantly negatively correlated after controlling for the influence of relevant factors; a company with higher proportion of major shareholders, and in company with lower degree of marketization, the negative correlation between political connections and crash risk is more significant; political links of non-foreign funded enterprises is more effective than political connections of foreign funded enterprises in reducing crash risk. The research results indicate that we should exert the positive influence of political connections, reduce the shareholding ratio of major shareholders, accelerate the process of marketization, strengthen corporate governance of non-foreign funded enterprise, and can reduce stock price crash risk, therefore, it will help steady operation of China’s capital market.